2009
DOI: 10.1037/a0014091
|View full text |Cite
|
Sign up to set email alerts
|

Family interactions in adoptive compared to nonadoptive families.

Abstract: Despite the large and growing numbers of adoptive families, little research describes interactions in families with adopted adolescents. Yet, adopted adolescents' increased risk for adjustment problems, combined with the association between family interactions and adolescent adjustment in nonadoptive families, raises questions about differences in adoptive and nonadoptive family interactions. We compared observed and self-reported family interactions between 284 adoptive and 208 nonadoptive families and within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 57 publications
(90 reference statements)
9
62
1
5
Order By: Relevance
“…But what is more characteristic of the current trend is its focus on family and relational processes. This can be illustrated, for instance, with reference to the analysis of interaction processes in families with and without adopted adolescents carried out by Rueter, Keyes, Iacono, & McGue (2009). This study found more similarities than differences in the way family members interacted with one another.…”
Section: Third Trend In Adoption Research: Underlying Processes and Fmentioning
confidence: 84%
“…But what is more characteristic of the current trend is its focus on family and relational processes. This can be illustrated, for instance, with reference to the analysis of interaction processes in families with and without adopted adolescents carried out by Rueter, Keyes, Iacono, & McGue (2009). This study found more similarities than differences in the way family members interacted with one another.…”
Section: Third Trend In Adoption Research: Underlying Processes and Fmentioning
confidence: 84%
“…Parental behavior is similar across adopted and nonadopted children (Rueter, Keyes, Iacono, & McGue, 2009) and adoptive parents are able to offer the child secure parent– child attachment relationships (Juffer, Bakermans–Kranenburg, & Van IJzendoorn, 2005). For adopted and nonadopted alike, both positive self-control and moral self-approval were connected to being brought up in expressive families that encouraged close and good communication (Kelly, Towner-Thyrum, Rigby,& Martin, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have only recently begun documenting adoptive family interactions and family factors that promote healthy outcomes for adopted adolescents (Palacios & Sánchez-Sandoval, 2005; Reuter, Keyes, Iacono, & McGue, 2009;Whitten, 2001). This paper Theoretical Perspectives…”
Section: Introductionmentioning
confidence: 97%